Observing The Limit Of Oscillation In Autocatalytic Reaction System - Nordin, Mohammad Juhairi (Universiti Sains Malaysia, 2021)
Autocatalytic reaction was one of the reactions where the concentrations of reactants intermediates form as products with periodicity. The presented by this thesis was using the Brusselator model which was one of the autocatalytic reaction systems. Autocatalysis has been widely explored in the form of models for the origin of life as a basis for self-organization. Chemical oscillation was analogous to oscillation where autocatalysis replaces positive feedback. In general, these reactions proceed evenly with varying the rates until at one point where it reaches equilibrium. Complex dynamical phenomena such as bistability, oscillations, deterministic instability, and random forming of spatial patterns or waves may occur in autocatalytic systems, which were undesirable in chemical production. The differentiation between first order and higher-order autocatalysis proved to be extremely useful. Both situations in which a single autocatalytic particle was active on the reactant side were classified as first-order autocatalysis.